Wear and frictional behaviour of partially oxidized and plasma sprayed NiCr and NiCrBSiFe coatings - Subbarao Medabalimi; Uzwalkiran Rokkala; Suresh Gudala; Netrananda Behera; M. R. Ramesh; Mesay Dejene (Scientific Reports)
Abstract The wear performance of partially oxidized NiCr and NiCrBSiFe coatings were investigated by varing load and speed. The partial oxidized powders were processed from the alloy powder using a flame spray process that involved spraying into distilled water. The partially oxidized powder was then plasma-sprayed onto MDN321 steel. The coatings were characterized for adhesive strength, microhardness, and density. The wear behavior was evaluated at disc speeds of 1, 2, and 3 m/s, with loads ranging from 10 to 50 N, over a 3000 m sliding distance. A significant difference in wear rates between the coating and substrate was observed. Operating at a sliding velocity of 1 m/s under a 10 N load, the substrate’s wear rate was found to be 3.56 times higher than that of the NiCrBSiFe coating, whereas for NiCr coating, it was 2.78 times higher. Wear rate coefficient performance shift takes place between the coatings at 12 N-m/s, product of applied load (C) and sliding velocity (V). In NiCrBSiFe coating, the wear mechanism observed at lower speeds and loads is micro-brittle and mechanism shifts to abrasive wear at higher speeds and loads. In the NiCr partially oxidized coating, the wear mechanism observed involves spallation of the coating at higher loads and adhesive wear at lower loads. Thermo gravimetric analysis of the coatings revealed a weight loss percentage of 1.42 for NiCrBSiFe and 14.09 for NiCr coatings. These findings highlight the NiCrBSiFe partially oxidized coating as being tenfold more stable at high temperatures compared to the NiCr partially oxidized coating.